MUSLIM INTENTION TO PARTICIPATE IN RETAIL CWLS: THE TEST OF MEDIATION AND MODERATION EFFECTS - Izra Berakon; Lu’liyatul Mutmainah; Abdul Qoyum; Hendy Mustiko Aji (Bank Indonesia, 2022)
Cash Waqf-Linked Sukuk (CWLS), which integrates cash waqf instruments and sovereign Sukuk, is an innovative Islamic investment product with social and spiritual dimensions. This study investigates public intention to participate in Retail CWLS (SWR) using the Technology Acceptance Model (TAM) framework with the addition of other relevant constructs. An online survey was conducted using the purposive sampling technique and involved 130 respondents. The data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) supported by WarpPLS. The results indicate that Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Perceived Transparency (PT), and Trust in the Indonesian Waqf Board and Waqf Institutions have a significant positive effect on individual Intention to participate in Retail CWLS. Furthermore, this study reveals that Trust could partially mediate the relationship between PU and individual Intention. However, Religiosity fails to moderate the relationship between PU and individual Intention to purchase SWR. The study also demonstrated other complementary statistical outputs such as split-sample, non-linear relationships among latent variables, effect size, and the Q-squared coefficient to ensure that the processed data were robust. Also, this finding indirectly implies that CWLS is not only targeted at the Muslim community but also for general investors from other religions and beliefs.